A NEW SPECIES OF Procamallanus (BAYLIS, 1923) FROM Mastacembalus armatus FROM IRIL RIVER, IMPHAL EAST, MANIPUR, INDIA - DEVI, N. PENGKI; BIDYALAKSHMI, T. H.; GAMBHIR, R. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
A new species of parasitic nematode Procamallanus Baylis, 1923 (Camallanidae) is described from the intestine of freshwater fish Mastacembalus armatus from Iril River, Imphal East, Manipur, India, collected during April-May, 2018. It has many different characters from known species which included the presence of faded lateral spiral ridges in the buccal cavity, a well developed lumen, extended upto the middle of the buccal cavity, 16 pairs of caudal preanal papillae in an arrangement of 8 pairs of subventral papillae, 2 pairs of ventral sessile papillae at cloacal opening and 6 pairs of post anal papillae with 1st and 3rd pair are pedunculated and 2nd, 4th and 6th pairs are ventrally sessile in male. The present specimen resembles with Procamallanus guptae (Arya,1978), Procamallanus berdii (Khan and Yaseen, 1969) and Procamallanus aspiculus Khera,1955 by the absence of spicules, but also differs in shape of buccal capsule, number of caudal papillae in males, presence of caudal alae, and shape of the tail in both sexes.